2015
DOI: 10.1159/000430248
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflamm-Aging Effects of Long-Term Caloric Restriction via Overexpression of SIGIRR to Inhibit NF-κB Signaling Pathway

Abstract: Background: Chronic inflammation is thought to be a determinant of the aging rate and longevity. Caloric restriction (CR) attenuates age-related increases in the systemic levels of several pro-inflammatory mediators, but the anti-inflammatory mechanisms of CR in the aging process remain unclear. Methods: Fisher 344 rats in a CR group were fed an amount of food corresponding to 60% of that fed to an ad libitum-fed (AL) group for 8 months. Biochemical analyses and renal pathological grading were used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…In addition, TLR4 and TLR9 were both downregulated as were numerous CCL chemokines in CTL CR mice, but only TLR9 and CCL1, 2, 20, and 22 met our cut-off parameters for statistical significance. These data support previous reports investigating the effects of long-term CR on NF-kB signaling (44) and inflammatory cytokines (45). The development of fibrosis and cirrhosis are established risk factors for the development of liver cancers including HCC (46).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, TLR4 and TLR9 were both downregulated as were numerous CCL chemokines in CTL CR mice, but only TLR9 and CCL1, 2, 20, and 22 met our cut-off parameters for statistical significance. These data support previous reports investigating the effects of long-term CR on NF-kB signaling (44) and inflammatory cytokines (45). The development of fibrosis and cirrhosis are established risk factors for the development of liver cancers including HCC (46).…”
Section: Discussionsupporting
confidence: 90%
“…Another study revealed that andrographolide could possess anti-cancer properties capable of modulating the TLR4/NF-κB signaling pathway in insulinoma [14]. The inflammatory response might be alleviated by single immunoglobulin IL-1-related receptor via blockade of the TLR4/NF-κB signaling pathway [15]. Despite the fact that the TLR4/NF-κB pathway has been extensively reviewed, studies investigating its potential effect on GERD, particularly on esophageal mucosal injury, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of IL‐1R8 is therefore relevant for the effects of IL‐37. Evidence reveals that expression of IL‐1R8 decreases with age in rats but that when rats were subjected to a calorie restricted diet, expression of IL‐1R8 increased . In that study, caloric restriction resulted in decreased NF‐κB expression.…”
Section: Mechanism Of Action: Il‐37 Receptorsmentioning
confidence: 75%
“…B). IL‐1R8 overexpression decreases the expression of MyD88, IL‐1 receptor‐associated kinase 4 (IRAK4), and tumor necrosis factor receptor‐associated factor 6 (TRAF6) . As shown in Figure B, IL‐1R8 functions as a sink for MyD88, depriving MyD88 from binding to the native TIR domain, resulting in a weak or no signal.…”
Section: Mechanism Of Action: Il‐37 Receptorsmentioning
confidence: 99%